CELLULOSIC MATERIALS AS POLYMER ELECTROLYTE MEMBRANE IN FUEL CELL APPLICATION - Radiman, Cynthia L.; Sarinastiti, A. (Center for Pulp and Paper, 2012)
Polymer Electrolyte Membrane Fuel Cells (PEMFC) and Direct Methanol Fuel Cell (DMFC) are considered as future power sources in overcoming the fossil-based energy crisis. The objective of this work is to explore one of the natural resources of Indonesia and to improve its properties by chemical modification in order to get the required characteristics as electrolyte membrane. In this work coconut water was used as the basic material. It was fermented by Acetobacter xylinum and the resulting bacterial cellulose was then phosphorylated using a microwave-assisted reaction. Those membranes have been immersed for a varied time ranging between 0 and 8 hours (0-8 h) in a mixture of N,N-dimethylformamide (DMF), phosphoric acid and urea prior to irradiation by microwave for 60 s. Those membranes were characterized by several methods, such as functional group analysis by FTIR, proton conductivity, ion exchange capacity, swelling index, morphology analysis by SEM and phosphorus content analysis by SEM-EDS. From the experimental data, it can be concluded that a phosphorylated bacterial cellulose prepared by a 4h–immersion could be used as an alternative electrolyte membrane for fuel cell applications.Keywords: fuel cell, bacterial cellulose, phosphorylated bacterial cellulose ABSTRAK Sel bahan bakar membran polimer eletrolit (PEMFC) dan sel bahan bakar metanol (DMFC) merupakan sumber energi masa depan yang dapat mengatasi krisis energi minyak bumi. Tujuan penelitian ini adalah untuk menggunakan bahan alam Indonesia yang dimodifikasi secara kimiawi supaya sifat-sifatnya dapat ditingkatkan untuk memenuhi persyaratan sebagai membran elektrolit. Dalam penelitian ini air kelapa telah digunakan sebagai bahan dasar dan selanjutnya difermentasi oleh Acetobacter xylinum. Selulosa bakterial yang dihasilkan difosforilasi dengan bantuan gelombang mikro. Membran tersebut direndam selama waktu yang bervariasi ( 0-8 jam) dalam campuran N,N-dimetilasetamida (DMF), asam fosfat dan urea sebelum diiradiasi dengan gelombang mikro selama 60 detik. Karakterisasi membran dilakukan dengan berbagai metoda, antara lain analisis gugus fungsi dengan FTIR, konduktivitas proton, kapasitas penukar ion, indeks penggembungan, analisis morfologi dengan SEM dan analisis kadar fosfor dengan SEM-EDS. Dari data yang diperoleh disimpulkan bahwa selulosa bakterial yang difosforilasi dengan proses perendaman selama 4 jam dapat digunakan sebagai alternatif untuk membran elektrolit dalam aplikasi sel bahan bakar.Kata kunci: sel bahan bakar, selulosa bakterial, selulosa bakterial terfosforilasi